DEVELOPMENT OF SPECTROPHOTOMETRIC AND FLUOROMETRIC METHODS FOR ESTIMATION OF DARUNAVIR USING QBD APPROACH - Godambe, R. D.; Disouza, J. I.; Jamkhandi, C. M.; Kumbhar, P. S. (International Journal of Current Pharmaceutical Research, 2018)
Objective: The main objective of the present study is to develop newer simple, precise spectrophotometric and fluorometric methods of estimation for Darunavir using coupling agent O-pthaladehyde. Methods: The experimental work was designed for both spectroscopic and fluorometric method development and validation. The method is based on formation complex of Darunavir with O-pthaladehyde. QbD approach was applied by varying different parameters. These parameters were designed into Ishikawa diagram. Results: The complex Darunavir-Phthalaldehyde in methanol with 0.1 N HCl showed linearity for both spectrophotometric and fluorometric methods. The calibration curve by spectrophotometry is linear in concentration range of 2-22 Âµg/ml with regression coefficient (R2) = 0.998 at 355 nm and for fluorometry it is linear in concentration range of 0.5-5.0 ng/ml with regression coefficient (R2) = 0.999. This method was found to be rugged and robust in different testing criteria with % RSD less than 2. The limit of detection and limit of quantification was found to be 0.2 Î¼g/ml and 0.8 Î¼g/ml for a spectrophotometric method and 0.12 Î¼g/ml and 0.43 Î¼g/ml for fluorometric method respectively. Conclusion: Both methods were found to be precise with % RSD of less than 2. The % recovery of the spectrophotometric and fluorometric methods was found to be 101.04 %, 98.15 % respectively. In this way, the results of all validation parameter were within the limits as per International Conference on Harmonization guideline. Â 